Respuesta :
The function is: f ( x ) = x³ - 2 x² - 68 x - 120
If f ( - 2 ) = 0, we have to divide this equation by: ( x + 2 )
( x³ - 2 x² - 68 x - 120 ) : ( x + 2 ) = x² - 4 x - 60
- x³ - 2 x²
--------------
- 4 x² - 68 x - 120
4 x² + 8 x
---------------------------
- 60 x - 120
60 x + 120
-----------------
0
After that for a function: f ( x ) = x² - 4 x - 60; f ( - 6 ) = 0
( x² - 4 x - 60 ) : ( x + 6 ) = x - 10
-x² - 6 x
-----------------
- 10 x - 60
10 x + 60
-------------
0
Answer:
C ) ( x - 10 ) ( x + 2 ) ( x + 6 )
If f ( - 2 ) = 0, we have to divide this equation by: ( x + 2 )
( x³ - 2 x² - 68 x - 120 ) : ( x + 2 ) = x² - 4 x - 60
- x³ - 2 x²
--------------
- 4 x² - 68 x - 120
4 x² + 8 x
---------------------------
- 60 x - 120
60 x + 120
-----------------
0
After that for a function: f ( x ) = x² - 4 x - 60; f ( - 6 ) = 0
( x² - 4 x - 60 ) : ( x + 6 ) = x - 10
-x² - 6 x
-----------------
- 10 x - 60
10 x + 60
-------------
0
Answer:
C ) ( x - 10 ) ( x + 2 ) ( x + 6 )